Real-Time Multiphoton Intravital Microscopy of Drug Extravasation in Tumours during Acoustic Cluster Therapy - Jessica Lage Fernandez; Sofie Snipstad; Astrid Bjørkøy; Catharina de Lange Davies (Cells, 2024)
Optimising drug delivery to tumours remains an obstacle to effective cancer treatment. A prerequisite for successful chemotherapy is that the drugs reach all tumour cells. The vascular network of tumours, extravasation across the capillary wall and penetration throughout the extracellular matrix limit the delivery of drugs. Ultrasound combined with microbubbles has been shown to improve the therapeutic response in preclinical and clinical studies. Most studies apply microbubbles designed as ultrasound contrast agents. Acoustic Cluster Therapy (ACT®) is a novel approach based on ultrasound-activated microbubbles, which have a diameter 5–10 times larger than regular contrast agent microbubbles. An advantage of using such large microbubbles is that they are in contact with a larger part of the capillary wall, and the oscillating microbubbles exert more effective biomechanical effects on the vessel wall. In accordance with this, ACT® has shown promising therapeutic results in combination with various drugs and drug-loaded nanoparticles. Knowledge of the mechanism and behaviour of drugs and microbubbles is needed to optimise ACT®. Real-time intravital microscopy (IVM) is a useful tool for such studies. This paper presents the experimental setup design for visualising ACT® microbubbles within the vasculature of tumours implanted in dorsal window (DW) chambers. It presents ultrasound setups, the integration and alignment of the ultrasound field with the optical system in live animal experiments, and the methodologies for visualisation and analysing the recordings. Dextran was used as a fluorescent marker to visualise the blood vessels and to trace drug extravasation and penetration into the extracellular matrix. The results reveal that the experimental setup successfully recorded the kinetics of extravasation and penetration distances into the extracellular matrix, offering a deeper understanding of ACT’s mechanisms and potential in localised drug delivery.